Spikelet sterility of wheat in farmer's field in Northwest Bangladesh (Bangladesh Journal of Botany, 2008)
In recent decades, sporadic and/or massive occurrence of spikelet sterility in wheat has been found in almost all the wheat growing areas of Bangladesh, especially in northwest Bangladesh where spikelet sterility causes yield reductions considerably. Investigations were carried out to understand the nature and probable cause(s) regarding the spikelet sterility problem in Bangladesh. Observations included varieties of wheat, sowing dates, prevailing weather and also soil boron (B) status in farmer's field of the sterility prone areas in northwest Bangladesh. It was found that the varieties Aghrani, Akbar and Kanchan had higher percentage of spikelet sterility than Sonalika. Seven days earlier sown wheat crops had more spikelet sterility, than seven days later sown ones, and it indicated the influence of environment and/or other cause(s) on spikelet sterility; but did not indicate the direct influence of soil boron, because, no remarkable difference of soil B status existed between the sterility affected and non-affected farmer's field in those areas. Key words: Wheat, Spikelet sterility, Grain set index, Bangladesh doi:10.3329/bjb.v37i2.1724 Bangladesh J. Bot. 37(2): 155-160, 2008 (December)